2021
DOI: 10.1002/er.7210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flow modes on operation characteristics of three‐dimensional non‐isothermal solid oxide fuel cell stack

Abstract: The three-dimensional non-isothermal model of anode-supported planar solid oxide fuel cell was established. In order to reduce the temperature rise of SOFC in the process of operation and improve the output performance of the stack, this paper studied and compared the operation of SOFC in four different flow modes. The study found that the flow mode has a great influence on the temperature distribution of the SOFC stack. In co-flow, the temperature increases continuously along the channel length. In the case t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
0
1
Order By: Relevance
“…While FARDADI [15] et al reversed the flow direction of air and fuel within the layers on the basis of cross-flow arrangement. The temperature distribution of the cell was improved, but some loss of power density was also observed, which is slightly different from the results of FAN [16] et al They applied the combination of inter-and intralayer inversion in an arrangement to a three-layer stack model, and found that the power density was improved to a certain extent. However, some of the above studies on new flow patterns only focus on the temperature change and ignore the power density [12][13][14] , while others draw contradictory conclusions on the change of power density and do not discuss the underlying reasons [15,16] .…”
Section: Introductioncontrasting
confidence: 84%
“…While FARDADI [15] et al reversed the flow direction of air and fuel within the layers on the basis of cross-flow arrangement. The temperature distribution of the cell was improved, but some loss of power density was also observed, which is slightly different from the results of FAN [16] et al They applied the combination of inter-and intralayer inversion in an arrangement to a three-layer stack model, and found that the power density was improved to a certain extent. However, some of the above studies on new flow patterns only focus on the temperature change and ignore the power density [12][13][14] , while others draw contradictory conclusions on the change of power density and do not discuss the underlying reasons [15,16] .…”
Section: Introductioncontrasting
confidence: 84%